1998
DOI: 10.1002/(sici)1097-4695(199812)37:4<541::aid-neu4>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Response of retinal ganglion cell axons to striped linear gradients of repellent guidance molecules

Abstract: Although molecular gradients have long been postulated to play a role in the development of topographic projections in the nervous system, relatively little is known about how axons evaluate gradients. Do growth cones respond to concentration or to slope? Do they react suddenly or gradually? Is there adaptation? In the developing retinotectal system, temporal retinal ganglion cell axons have previously been shown to avoid repellent cell‐surface activities distributed in gradients across the optic tectum. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…4,5,19,33,38 We analyzed our data from single-cue gradient experiments in the context of the two models of gradient detection: absolute change (to which we refer as slope) and fractional change in concentration. Within our system, the molecular concentration varied linearly across the 250 lm width of each gradient channel, as confirmed by immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,19,33,38 We analyzed our data from single-cue gradient experiments in the context of the two models of gradient detection: absolute change (to which we refer as slope) and fractional change in concentration. Within our system, the molecular concentration varied linearly across the 250 lm width of each gradient channel, as confirmed by immunofluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,25 Experimental work has suggested that axons could be guided by a wide range of parameters including the absolute molecular concentration, the gradient sign or direction, the gradient shape, the gradient slope or steepness, and the fractional change in concentration. 3,16,19,33,38,43 Previous studies of axon guidance by gradients have largely focused on examining diffusible gradients of soluble molecules such as neurotrophic factors, semaphorins, and netrins. 2,3,21,27,38 Recently, gradients of soluble cues have been deposited on the surfaces of three-dimensional collagen gels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, if the axon has sufficiently explored the local environment and can no longer lower d, it may decide to stop at its current position. This proposition may be corroborated by empirical evidence showing that axons tend to stop at a defined ephrin concentration regardless of the slope of the ligand gradient (Rosentreter et al, 1998). Thus, d may itself constitute a second stop signal used by the axon.…”
Section: The Density Function Is Linear In the Interval [1max(v)]mentioning
confidence: 75%
“…While nasal axon growth was not affected by the gradient in this assay, temporal axons grew an amount that was negatively correlated with the steepness of the gradient (i.e., the steeper the gradient, the shorter the axons). Using a more refined version of this technique, Rosentreter et al (1998) then suggested that temporal axons grow up a gradient of posterior tectal membranes until they have travelled a fixed increment of concentration that is independent of both the slope of the gradient and the starting concentration. However, this conclusion relies on strong quantitative inferences drawn from somewhat qualitative criteria for assessing the stopping point of the front of axons within a lane.…”
Section: Systems-level Experiments To Test the Chemoaffinity Hypothesismentioning
confidence: 99%